Optimizing Financial Management: Looking at the Story Behind the Saving Passion of Padangsidempuan City High School Students - Novebri; Hakim, Andy; Alfian, Ian (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2024)
The cultivation of true character starts from an early age in children, until they continue into adulthood. Character education is carried out in some ways, one of way is financial education through savings activities at school, either independently through the class treasurer or directly with the bank that comes to school. This research took place from March - May 2023 at eight high schools in the city of Padangsidempuan, which aims to know financial education and its impact on character building, involving students and teachers as the main informants, using the case study method through interviews and direct observation at schools. The results of the research found that (1) financial education is carried out in three ways, namely saving through class cash, saving through the bank, and saving independently at home using a piggy bank, (2) since Covid-19 there are no more banks coming to schools to quote savings to students who want to save, (3) students' low interest in saving, (4) most high school schools in the city of Padangsidempuan do not accommodate financial education through class cash savings activities. The low interest in saving money at high schools in the city of Padangsidempuan is caused by several things, such as the low or underprivileged economic conditions of students' families.